Midwives' attitudes, beliefs and concerns about childhood vaccination: A review of the global literature. Issue 44 (22nd October 2018) - Attwell, K.; Wiley, K.E.; Waddington, C.; Leask, J.; Snelling, T.
Highlights: There is limited research published on Midwives' immunisation attitudes and practice. The majority of midwives support immunisation, however a spectrum of beliefs and concerns emerged. The reservations expressed focussed on what is not yet known rather than mistrust of current evidence. The midwifery focus on the individual and parental choice has implications for immunisation promotion. Abstract: Vaccine hesitancy in industrialised countries is an area of concern. Health professionals play a significant role in parental vaccination decisions, however, to date the role of midwives has not been widely explored. This review sought to describe the attitudes and communication practices of midwives in developed countries towards childhood vaccines. Medline, Cinahl, PsychInfo, Embase and the grey literature were searched. Inclusion criteria were qualitative and quantitative studies reporting midwives' beliefs, attitudes and communication practices toward childhood vaccination. The search returned 366 articles, of which 359 were excluded by abstract. Two additional articles were identified from the grey literature and references, resulting in nine studies from five countries included in the review. Across the studies, the majority of midwives supported vaccination, although a spectrum of beliefs and concerns emerged. A minority expressed reservations about the scientific justification for vaccination, which focussed on what is not yet known rather than mistrust of current evidence. Most midwives felt that vaccines were safe; a minority were unsure, or believed they were unsafe. The majority of midwives agreed that childhood vaccines are necessary. Among those who expressed doubt, a commonly held opinion was that vaccine preventable diseases such as measles are relatively benign and didn't warrant vaccination against them. Finally, the midwifery model of care was shown to focus on providing individualised care, with parental choice being placed at a premium. The midwifery model care appears to differ in approach from others, possibly due to a difference in the underpinning philosophies. Research is needed to understand how midwives see vaccination, and why there appears to be a spectrum of views on the subject. This information will inform the development of resources tailored to the midwifery model of care, supporting midwives in advocating for childhood vaccination.